Study on the influence of environmental regulation on the environmentally friendly behavior of farmers in China - Zhao, Jiajia; Liu, Lingzhi; Qi, Jianling; Dong, Jinpeng (Frontiers in Environmental Science, 2022)
Livestock breeding waste is an important problem in rural environmental pollution management, and waste pollution prevention is an important part of realizing rural civilization construction and low-carbon recycling production. Based on survey data from farmers in large meat duck breeding provinces, this article analyzes the influence of environmental regulations on meat duck farmers' environmentally friendly behavior from the perspective of the cost effect and Porter effect through a probit model. In addition, the potential role of risk perception is explored by analyzing the heterogeneity of farmers' environmentally friendly behavior at different breeding scales. The results show that the intensity of environmental regulation and the environmentally friendly behavior of meat duck farmers have an inverted U-shaped relationship; different environmental regulations significantly affected the environmentally friendly behavior of farmers. Among them, the guiding regulation plays a significant positive role in the resulting environmentally friendly behavior of farmers in terms of constraint regulation and incentive regulation. There is heterogeneity in the impacts of environmental regulation on the environmentally friendly behaviors of farmers of different scales. Risk cognition has a partial mediating effect in the effects of constraint regulation, incentive regulation and guidance regulation on farmers' environmentally friendly behavior. To promote farmers' awareness of waste environmental pollution control and the implementation of environmentally friendly behaviors, the government should carry out appropriate environmental regulation policies according to local conditions and strengthen relevant technical training, publicity and promotion to improve farmers' performance and optimize the resource allocation of meat duck breeding, thereby promoting the efficiency and industrial competitiveness of meat duck breeding and realizing low-carbon and healthy meat duck breeding.